The family in question: immigrant and ethnic minorities in multicultural Europe - Grillo, Ralph D. (IMISCOE research, 2008)
"The family lives of immigrants and ethnic minority populations have become central to arguments about the right and wrong ways of living in multicultural societies. While the characteristic cultural practices of such families have long been scrutinized by the media and policy makers, these groups themselves are beginning to reflect on how to manage their family relationships. Exploring case studies from Austria, the Netherlands, Norway, Portugal, Spain, Switzerland, the United Kingdom, and Australia, The Family in Question explores how those in public policy often dangerously reflect the popular imagination, rather than recognizing the complex changes taking place within the global immigrant community"--Publisher's description